Good Communication for Entrepreneurial Literacy at Pesantren - Yulianti; Ike Junita Triwardhani; Endri Listiani (Mediator: Jurnal Komunikasi, 2023)
Entrepreneurship greatly contributes to increasing competitiveness, creating jobs, gaining career opportunities, and accelerating economic growth. There have been many studies related to entrepreneurship, but unfortunately, none of them has reviewed the competency framework of entrepreneurship as a life skill, especially in pesantren (Islamic boarding schools). The purpose of this research is to provide an overview of the state of entrepreneurial literacy and skills based on its competency framework. This study describes how to obtain ideas and opportunities, map the resources owned, and take actions to map the entrepreneurial culture built by pesantren. This research is conducted at Pesantren Sirojul Huda. The method used is a qualitative descriptive research method with data collection techniques through interviews and observation. As a result, three thematic areas: (1) ideas and opportunities, (2) resources, and (3) into action, it was found that the mapping of Islamic boarding school entrepreneurial culture was going well, and synergy between the parties in the Islamic boarding school was created thanks to the interpersonal communication carried out. Interpersonal communication has a big role in making this happen.